Core Competence in Fundamental Nursing Practicum Scale: A validity and reliability analysis. (July 2022) - Chang, Yu-Hsuan; Huang, Shu-He; Shun, Shiow-Ching; Lin, Pao-Chen
Abstract: Aim: This study aimed to develop and examine the psychometric properties of validity and reliability of the Core Competence in Fundamental Nursing Practicum Scale. Background: Fundamental nursing practicum is an initial practicum required for nursing students; however, no measurement tool is available to assess students' core competence during their first practicum. Design: Cross-sectional design. Methods: Nursing students from six nursing colleges in Southern Taiwan who completed their fundamental nursing practicum within 1 month were recruited. The initial 39-item Core Competence in Fundamental Nursing Practicum Scale was drafted and examined for its content, face and factorial validity. The data were randomly assigned into two subgroups and analyzed using exploratory and confirmatory factor analyses. Exploratory factor analysis was performed using principal-axis factoring and direct oblimin rotation and numbers of factors were extracted on the basis of eigenvalues > 1 and a scree plot. The exploratory factor analysis derived structure was then verified by a confirmatory factor analysis using maximum likelihood estimation. Reliability was examined in term of internal consistency. Results: The exploratory factor analysis and confirmatory factor analysis samples comprised 405 and 513 students, respectively. Four items were omitted by content validity and another four items were omitted because of the ceiling effect. Six items were removed during the exploratory factor analysis because of their lower factor loadings (< 0.4). The final 25-item Core Competence in Fundamental Nursing Practicum Scale comprised 5 domains, namely communication (3 items), application of nursing process (6 items), basic biomedical science (4 items), nursing skills and ability to perform a care process (7 items), and professional attitude (5 items), which collectively explained 70.14% of total variance. The structure was then verified by a confirmatory factor analysis with satisfactory model fit. The Cronbach's alpha of the Core Competence in Fundamental Nursing Practicum Scale was 0.94. Conclusions: The 25-item Core Competence in Fundamental Nursing Practicum Scale reliably and validly measures nursing students' core competence during their fundamental nursing practicum. Instructors can use the scale to identify students' weak core competencies and refine their courses for novice nurses.